(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
For the construction of civil engineering works, concrete play main role and a large quantum of concrete is being utilized. Both coarse aggregate and fine aggregate which is a major constitute used for making conventional concrete, has become highly expensive and also scarce. The investigation was prepared to examine the harden properties of concrete on the replacement of cement with silica fumes and fine aggregate with the carbon fibers. Carbon fibers are thin, tough and adjustable so it has high tensile strength, low weight, high chemical resistance, low thermal expansion and have tolerance to high temperatures. Silica fume has impact on various characteristics of fresh and cured concrete including increase in workability and lowering bleeding and segregation. One nominal mix was prepared and combination mixes were prepared. M35 grade was used for mix design. The harden properties of concrete like compression, split and flexural strength was examined on replacement of cement with silica fumes and fine aggregate with carbon fibers. The percentage replacement was taken as 0%, 5%, 10%, and 20% for silica fumes and fine aggregate with carbon fibers with 0%, 2.5%, 5 % and 7.5%. The cylindrical specimens, cubes and beams were prepared for testing after the recommended curing period of 7 days and 28 days respectively.